2006
DOI: 10.1002/jclp.20305
|View full text |Cite
|
Sign up to set email alerts
|

Coping variables that mediate the relation between intimate partner violence and mental health outcomes among low-income, African American women

Abstract: Coping variables that mediate the relation between intimate partner violence (IPV) and mental health outcomes among African American women were investigated. The study sample included 143 economically disadvantaged African American women ranging in age from 21 to 64 years old who were receiving services at an urban public health system. Sixty-five had experienced IPV within the past year and 78 had never experienced IPV. Results indicated that (a) the IPV status-depressive symptoms link was mediated by multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
97
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(107 citation statements)
references
References 72 publications
(83 reference statements)
8
97
1
Order By: Relevance
“…Necessary to note, a growing body of research suggests socioeconomic status more accurately predicts victimization risk than race as mentioned previously (Logan et al, 2006;Mitchell, et al, 2006). Thus, poor women who also experience any of the previously mentioned risk factors are at an even higher risk for experiencing victimization than women with higher socioeconomic status (Breiding, et al, 2008;Logan et al, 2006).…”
Section: Adult Victimization (Construct 1)mentioning
confidence: 99%
See 4 more Smart Citations
“…Necessary to note, a growing body of research suggests socioeconomic status more accurately predicts victimization risk than race as mentioned previously (Logan et al, 2006;Mitchell, et al, 2006). Thus, poor women who also experience any of the previously mentioned risk factors are at an even higher risk for experiencing victimization than women with higher socioeconomic status (Breiding, et al, 2008;Logan et al, 2006).…”
Section: Adult Victimization (Construct 1)mentioning
confidence: 99%
“…al, 2001;Hill, Kaplan, French, & Johnson, 2010). Results from a study conducted by Hill and colleagues (2010) (Borelli, Goshin, Joestl, Clark, & Byrne, 2010;Cohen & Wills, 1985;Coker et al, 2002b;Coker, Watkins, Smith, & Brandt, 2003;Collins, & Feeney, 2004;Crouch, Milner, & Caliso, 1995;Kendler, Gardner, & Prescott, 2002;Mitchell et al, 2006;Mburia-Mwalili et al, 2010;Nurius et al, 2003). Brewin and colleagues' meta-analysis (2000) found that a lack of social support is a significant risk factor for post-traumatic stress.…”
Section: Cumulative Victimization and Psychological Distress (Correlamentioning
confidence: 99%
See 3 more Smart Citations